2012
DOI: 10.1044/1092-4388(2011/10-0238)
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Broad Auditory Filters for Identification of Multichannel-Compressed Vowels

Abstract: Purpose In view of previous findings (Bor, Souza & Wright, 2008) that some listeners are more susceptible to spectral changes from multichannel compression (MCC) than others, this study addressed the extent to which differences in effects of MCC were related to differences in auditory filter width. Method Listeners were recruited in three groups: listeners with flat sensorineural loss, listeners with sloping sensorineural loss, and a control group of listeners with normal hearing. Individual auditory filter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…For example, while short RT may have been relatively more beneficial for some listeners due to the rapid increase in gain for low-intensity parts of speech, it may have been relatively more disadvantageous for others by increasing the noise floor ( i.e ., ambient noise in the recorded signal in this study or ambient room noise combined with microphone noise in the real world), thereby reducing the salience of information conveyed by temporal envelope in the presence of the masker (Plomp, 1988; Drullman et al ., 1994; Souza & Turner, 1998; Stone & Moore, 2003; 2007; Jenstad & Souza, 2005, 2007; Souza & Gallun, 2010). Similarly, while use of multiple channels may have relatively more beneficial for some listeners because gain for low-intensity speech could be rapidly increased in frequency-specific regions when and where it was needed the most (e.g., Yund & Buckles, 1995a; Henning & Bentler, 2008), it may have been relatively more disadvantageous for others because the increased gain for low-intensity frequency regions may have reduced the salience of information conveyed by spectral shape, including formant peaks and spectral tilt (Yund & Buckles, 1995b; Franck et al ., 1999; Bor et al ., 2008; Souza et al ., 2012). Furthermore, if the low-intensity temporal and spectral segments consisted primarily of noise, increased masking may have resulted (Plomp, 1988; Edwards, 2004).…”
Section: Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while short RT may have been relatively more beneficial for some listeners due to the rapid increase in gain for low-intensity parts of speech, it may have been relatively more disadvantageous for others by increasing the noise floor ( i.e ., ambient noise in the recorded signal in this study or ambient room noise combined with microphone noise in the real world), thereby reducing the salience of information conveyed by temporal envelope in the presence of the masker (Plomp, 1988; Drullman et al ., 1994; Souza & Turner, 1998; Stone & Moore, 2003; 2007; Jenstad & Souza, 2005, 2007; Souza & Gallun, 2010). Similarly, while use of multiple channels may have relatively more beneficial for some listeners because gain for low-intensity speech could be rapidly increased in frequency-specific regions when and where it was needed the most (e.g., Yund & Buckles, 1995a; Henning & Bentler, 2008), it may have been relatively more disadvantageous for others because the increased gain for low-intensity frequency regions may have reduced the salience of information conveyed by spectral shape, including formant peaks and spectral tilt (Yund & Buckles, 1995b; Franck et al ., 1999; Bor et al ., 2008; Souza et al ., 2012). Furthermore, if the low-intensity temporal and spectral segments consisted primarily of noise, increased masking may have resulted (Plomp, 1988; Edwards, 2004).…”
Section: Discusssionmentioning
confidence: 99%
“…Listeners with SNHL tend to have more difficulty processing changes in spectral shape and maintaining an internal representation of spectral peak-to-valley contrasts (e.g., Bacon & Brandt, 1982; Van Tassel et al ., 1987; Leek et al ., 1987; Turner et al ., 1987; Summers & Leek, 1994; Henry & Turner, 2003). An additional reduction in spectral contrast from multichannel WDRC can diminish the perception of speech sounds whose phonemic cues are primarily conveyed by spectral shape, for example, vowels, semivowels, nasals, and place of articulation for consonants (Yund & Buckles, 1995b; Franck et al ., 1999; Bor et al ., 2008; Souza et al ., 2012). Thus, performance for WDRC with short RTs, which also degrades temporal envelope cues, might decrease once the number of channels is increased beyond the point at which additional channels no longer optimize audibility (Stone & Moore, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Souza et al (2012b) evaluated the effect of temporal envelope distortion on consonant features using spectrally degraded vowel-consonant-vowel (vCv) nonsense syllable tokens presented to listeners with normal hearing. They reported that under spectrally degraded conditions, listeners' scores decreased with increases in envelope distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Listeners might have been able to shift their attention to alternative cues to offset the impact of envelope distortions. With hearing loss which results in broader auditory filters, spectral cues may be less available (Tyler, Hall, Glasberg, Moore, & Patterson, 1984; Souza, Wright, Bor, submitted), and the importance of the envelope may be increased (Boothroyd, Springer, Smith & Schulman, 1988; Davies-Venn, 2010). Spectral cues will be even more limited for cochlear implant wearers, who typically receive only four to eight channels of spectral information (Friesen, Shannon, Baskent & Wang, 2001).…”
mentioning
confidence: 99%